University Service Quality: The Impact of Student Satisfaction and Loyalty in Public Universities of Bangladesh - Mahamudul Hasan; Md. Zakir Hosen (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
The present study explores the effect on student satisfaction and student loyalty of higher education service quality dimensions. Ensuring quality improvement and implementation of strategies for the tertiary education sector has become critical. Moreover, the study also tests the mediating impact of university reputation and external prestige between university service quality and satisfaction and loyalty. Data has collected through a structured questionnaire from a sample of 390 graduate and undergraduate students of two public universities in Bangladesh. The study reflects that the performance on service quality dimensions of selected public universities is not satisfactory. The study results have shown that Teaching, Support services, Library and lab facilities, and internationalization significantly influence student satisfaction except for Administrative service and Hostel facilities. Teaching, Administrative Services, Library and lab facilities, and internationalization significantly influence student Loyalty. The mediating analysis has shown that student satisfaction partially mediates between service quality and student loyalty. The study results have also indicated that university reputation and external prestige partially mediate between service quality and student satisfaction and loyalty. The previous studies which measure service quality of Bangladeshi higher educational institutions have applied the SERVQUAL model, which is not suitable for an educational institution. However, this study has applied a higher education service quality model uniquely developed to measure higher educational institutions' service quality.